Nanoporous microparticles of cellulose nanofibrils: The effect of fluid bed atmospheric spray freeze drying - Silva, J. M. (2025)
Cellulose nanofibers are abundant, low-cost, biodegradable and non-toxic materials that are a technological alternative for products in pharmaceutical field. The aim of this study was to investigate the effect of fluid bed atmospheric spray freeze drying on cellulose nanofibers characteristics, and compare to conventional spray and freeze drying methods. The atmospheric spray freeze dried nanofibers had moisture content of 2.3 %, mean size 4.0 μm, circularity of 0.86 and angle of repose of 27.3°. Also, solid state evaluation of atmospheric spray freeze dried cellulose nanofibers and other samples showed very similar chemical and thermal characteristics, but a relative crystallinity of 45.3 %, similar to spray dried powders. Furthermore, the most important feature of atmospheric-spray-freeze-dried cellulose nanofibers is their morphology, since unlike the other methods those resulted in highly nanoporous structures. The atmospheric-spray-freeze-drying of cellulose nanofibers may become a new and attractive alternative for the preparation of microsponges for pharmaceutical applications.